2021
DOI: 10.1016/j.envint.2021.106845
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to parabens and early childhood BMI z-scores – Associations between placental ethyl paraben, longitudinal BMI trajectories and cord blood metabolic biomarkers

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 109 publications
2
11
0
Order By: Relevance
“…The results can be supported from a laboratory animal study that reported increased activity of serum glutamic oxalacetic transaminase (aspartate aminotransferase, AST), alanine transaminase (ALT), and STB in mice exposed to IMI. , Glutamyltransferase (GGT) is an enzyme located on the outer surface of liver cells that catalyzes glutathione uptake and participates in intracellular antioxidant defense and pro-oxidant processes. High serum GGT activity is considered to be a biomarker of hepatobiliary toxicity . Positive correlations were also observed between of-IMI and uric acid (UA, β = 0.040 μmol/L, 95%CI: 0.006, −0.074) and urea (β = 0.041 mmol/L, 95%CI: 0.000, 0.081) in MS, similar to that found in exposed rats .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The results can be supported from a laboratory animal study that reported increased activity of serum glutamic oxalacetic transaminase (aspartate aminotransferase, AST), alanine transaminase (ALT), and STB in mice exposed to IMI. , Glutamyltransferase (GGT) is an enzyme located on the outer surface of liver cells that catalyzes glutathione uptake and participates in intracellular antioxidant defense and pro-oxidant processes. High serum GGT activity is considered to be a biomarker of hepatobiliary toxicity . Positive correlations were also observed between of-IMI and uric acid (UA, β = 0.040 μmol/L, 95%CI: 0.006, −0.074) and urea (β = 0.041 mmol/L, 95%CI: 0.000, 0.081) in MS, similar to that found in exposed rats .…”
Section: Resultssupporting
confidence: 69%
“…High serum GGT activity is considered to be a biomarker of hepatobiliary toxicity. 76 Positive correlations were also observed between of-IMI and uric acid (UA, β = 0.040 μmol/L, 95%CI: 0.006, −0.074) and urea (β = 0.041 mmol/L, 95%CI: 0.000, 0.081) in MS, similar to that found in exposed rats. 77 These results suggest that of-IMI is hepatotoxic and nephrotoxic.…”
Section: Chemicals Andsupporting
confidence: 66%
“…Biological matrices were collected at various gestational ages, with urine as the predominantly measured biological matrix. A few studies measured paraben concentrations using placentae or amniotic fluid [ 28 , 29 , 30 , 31 ]. The majority of these studies showed that parabens could cross the placental barrier [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…A few studies measured paraben concentrations using placentae or amniotic fluid [ 28 , 29 , 30 , 31 ]. The majority of these studies showed that parabens could cross the placental barrier [ 28 , 29 , 30 , 31 ]. Early life exposure to parabens is associated with increases in the gestational weight gain (GWG) rate [ 32 ], changes in height, head, hip, or arm circumference [ 28 , 30 , 33 , 34 ], z-scores of bodyweight [ 35 ], BMI or BMI z-scores [ 31 , 36 , 37 ], and overweight status in early childhood [ 38 ], although the direction of associations depends on the type of parabens and gender ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation